RefLex: Reference Lexicon of the languages of Africa - (:unkn) unknown (My University, 2011)
RefLex is an online database (www.reflex.cnrs.fr) containing lexical data from nearly 900 languages of Africa. The web interface includes searching modules but also provides online tools that are of great interest for linguistic research, such as the managament of cognates and phonetic correspondances, phonological statistics, maps, etc.
Keywords: African Research